Implementasi Modul Pembelajaran Berbasis Virtual Reality untuk Pendidikan Kedokteran - Al Hafidz, Ilham Achmad; Sukaridhoto, Sritrusta; Muhammad Udin Harun Al Rasyid; Rizqi Putri Nourma Budiarti; Rachma Rizqina Mardhotillah; Rizki Amalia; Evianita Dewi Fajrianti; Naufal Adi Satrio; Amma Liesvarastranta Haz (AI Society & STMIK Indonesia, 2022)
The Corona-Virus Disease 2019 (COVID-19) pandemic has impacted all levels of society and has disrupted all aspects of life, including education. On the other hand, the current crisis is rekindling the need for online learning opportunities and virtual education programs. Most medical schools have responded to this by turning to online or video-based learning. In the face of a pandemic, maintaining standards in medical education, keeping clinical knowledge on track, and minimizing assessment disruptions are complex tasks to complete. This new environment requires adaptation to prepare future doctors for their roles better. This research will implement an immersive medical learning platform by integrating the real immersive experience of Virtual Reality (VR) into medical education. The use of VR in this study has given satisfaction to users through the PIECES framework analysis by getting a score between 3.9 - 4.2 from the measurement of user satisfaction which means that users are satisfied with the offerings and services of this platform.